The effect of Wastewater from the Dorah Refinery Treatment Unit on Lycopersicon esculentum Mill. Tomato Grown in Three Types of Soil - Al-Saadi, Hussein jassim Muhammad; Al-Shammary, Maher Zaki Faisal (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The main objective of this study is to evaluate the effects of waste water from the Dora refinery’s treatment unit on tomato Lycopersicon esculentum grown in three types of soil taken from the same area, with consideration to the number of leaves, lycopene, and beta-carotene content in tomato yield, as well as the plant’s ability to absorb the toxic compounds furfural and -1, 2 dibromoethane. The experiment was carried out using pots in the glass house belonging to the Department of Biology, College of Education for Pure Sciences/Ibn Al-Haytham, University of Baghdad, for the seasons 20/9/2022–19/3/2023. The experiment included 45 treatments with 3 types of soil (clay, mixed, and sandy), and each type of soil had 5 treatments with 3 replicates. Control plants were left without treatment for each type of soil. The soil was sprayed with different volumes of water discarded from the treatment unit (0.1, 0.2, 0.3, and 0.4 ml/kg) before planting, and adding the same treatments with irrigation water was repeated after 53 days of planting at the stage of 4-6 leaves. The results showed that the treatment exceeded 0.1 ml. kg-1 soil in leaf area, number of leaves, lycopene, and beta-carotene content, as it gave the highest mean with an increase of 16.48%, 7.52%, 1.21%, and 0.54%, respectively, compared to untreated plants. As for the ability of the fruits to store furfural and 1,2-dibromoethane, it reached the highest average with a volume of 0.4 ml. kg-1 soil. The results also indicated that the mixed soil was superior in all traits except for the fruit content of furfural, which was superior to the clay soil.